Caracterización de la fauna de vertebrados atropellada en la carretera br 174, amazonas, brasil - Omena Junior, Reynie; Pantoja Lima, Jackson; Wendt Santos, André Luis; Aguiar ribeiro, Gyovanni Augusto; Aride, Paulo Henrique (Universidad de Sucre: Facultad de Ciencias Agropecuarias, 2012)
The pavement of highway BR-174 in the year of 1996, favored the development of economic activity and development the town. However, that road it dammed courses d' water and in this time, his margins were busy by peoples, bathers and by communities, giving initiate to the colonization and occupation of the same one. The wild fauna had his divided territory by the trail of asphalt, which way vehicles for the town of Presidente Figueiredo, for Roraima and to for the Venezuela. The present study had for objective, study the impact of the Highway BR- 174 about the fauna of vertebrates in road Manaus - President Figueiredo, in the State of the Amazon. They were carried out 111 surveys, in the period of March of 2003 to March of 2005. The animals knocked down were identified with use a guide of field, noted the equivalent kilometers and the date. As they turned out, twenty-seven species of wild animals were knocked down and dead, being that the more reached were to Common Opossum Didelphis marsupialis, (129 individuals), dog Canis lupus familiaris (23), Collared Anteater Tamandua tetradactyla and the Giant Marine Toad Rhinella marina, Coragyps atratus, (22 each), vulture (9) and the cat Felix catus (8). For it reduce and low the impact of that highway about the native fauna, is urgent the need of be established signals and limits of speed in the local of bigger incidence of accidents and promote a campaign of education for the traffic in that highway. La pavimentación de la carretera BR-174, en 1996 ayudó a incrementar la actividad económica y el desarrollo del municipio. Sin embargo, esta carretera represó ríos y con el tiempo, sus márgenes fueron ocupadas por los agricultores, los bañistas y de las comunidades, dando origen a la colonización y la ocupación de los mismos. La fauna tuvo su territorio dividido por una pista de asfalto, donde los vehículos viajan a la ciudad de Presidente Figueiredo, al estado de Roraima hasta Venezuela. El presente estudio tuvo como objetivo estudiar el impacto de la carretera BR-174 ...